General Psychology for Honors Students - Votaw, Kate (2020)
What are the most effective methods to study for a test? What are the meanings of dreams? How do illusions work? With whom are you most likely to fall in love? These are just a few of the questions that have been asked by psychologists since the birth of the field as an area of scientific research in the 1870’s. This text surveys the basic concepts, theories, and pivotal findings over the past 100 years in the science of Psychology, with special emphasis on contemporary concepts and findings focused on the relation of the brain to normal and pathological behaviors. Psychology has long evolved past the psychodynamic influence to include biological, social, learning, motivational, and developmental perspectives, to name a few. Contemporary psychologists go beyond philosophical or anecdotal speculation and rely on empirical evidence to inform their conclusions. Similarly, readers will push beyond pre-existing schemas and misconceptions of the field of psychology to an understanding of contemporary quantitative research methods as they are used to predict and test human behavior. This textbook is a compilation of thirty-nine readings organized into ten sections. Introduction to Psychology (Readings 1 - 5) A brief history of psychology, followed by an introduction to contemporary psychology, an overview of the scientific method, an introduction to research design, and thinking like a psychological scientist. Psychophysiology (Reading 6 - 8) Neurons, how our brain controls our thoughts, feelings, & behavior, and an introduction to psychophysiological methods in neuroscience. Consciousness & Sleep (Readings 9 - 12) The nature of consciousness, an exploration of sleep, why we sleep, the stages of sleep, and sleep problems and disorders. Perception (Readings 13 - 14) Seeing, and on the accuracy and inaccuracy of perception. Healthy Living (Readings 15 - 16) A healthy life, and substance use & abuse. Learning & Memory (Readings 17 - 20) Learning and memory, predictive learning, operant conditioning, memories as types and stages, and how we remember, with cues to improving memory. Social Psychology (Readings 21 to 26) Conformity, obedience, power & leadership, how the social context influences helping, and determinants of helping, gender and prejudice & discrimination. Psychological Development (Readings 27 to 30) Cognitive development in childhood, theories of development, and attachment through the life course. Research methods in developmental psychology. Personality & Psychological Disorders (Readings 31 - 37) Personality, psychological disorders, diagnostics and classification, anxiety disorders, mood disorders, schizophrenia spectrum disorders, and personality disorders. Treatment (Readings 38 - 39) Therapeutic orientations and psychopharmacology. Changes to the original OER works were made by Kate Votaw and Judy Schmitt to suit the needs of the Inquiries in the Social and Behavioral Sciences course in the Pierre Laclede Honors College at the University of Missouri-St. Louis. This work was developed with support from the University of Missouri-St. Louis Thomas Jefferson Library, with special thanks to librarians Judy Schmitt and Helena Marvin